School effectiveness factors in the use of the laptops of the OLPC Program (Revista Peruana de Investigación Educativa, 2014)
This paper analyzes which variables related with the provision of XO laptops from the One Laptop per Child (OLPC) program are linked with higher achievement in reading comprehension, math achievement, cognitive skills, and abilities to use the laptops. We used the data collected for the impact evaluation of the OLPC program in Peru in 2010 (Cristia, Ibarrarán, Cueto, Santiago y Severin, 2012). Using a multivariate linear model with geographic strata fixed effects we conducted a secondary analysis of this data, and found that, after controlling for several covariates, those teachers with higher skills in the use of the laptops had students with higher performance in all areas. We also found that the frequency and intensity of laptop use, both by teachers and by students, was associated with the ability to use these tools.
Keywords: academic achievement; educational effectiveness; educational technology; XO laptops; OLPC